9(n+7)+3(n-2)=

Simple and best practice solution for 9(n+7)+3(n-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(n+7)+3(n-2)= equation:


Simplifying
9(n + 7) + 3(n + -2) = 0

Reorder the terms:
9(7 + n) + 3(n + -2) = 0
(7 * 9 + n * 9) + 3(n + -2) = 0
(63 + 9n) + 3(n + -2) = 0

Reorder the terms:
63 + 9n + 3(-2 + n) = 0
63 + 9n + (-2 * 3 + n * 3) = 0
63 + 9n + (-6 + 3n) = 0

Reorder the terms:
63 + -6 + 9n + 3n = 0

Combine like terms: 63 + -6 = 57
57 + 9n + 3n = 0

Combine like terms: 9n + 3n = 12n
57 + 12n = 0

Solving
57 + 12n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-57' to each side of the equation.
57 + -57 + 12n = 0 + -57

Combine like terms: 57 + -57 = 0
0 + 12n = 0 + -57
12n = 0 + -57

Combine like terms: 0 + -57 = -57
12n = -57

Divide each side by '12'.
n = -4.75

Simplifying
n = -4.75

See similar equations:

| 4x^2-3x=2x-x^2 | | (-3)-(-5)= | | 7(n+1)+7(n+5)= | | -2(a-3b)-(2a-b)= | | 3x+99=-99-9x | | (x-2)-x(x-2)=0 | | 0.3333(15x+975)=4000 | | 5-2p=15-3p | | (5x+3)+(5x-3)+90=180 | | -p*p= | | y^2-2y+1=16 | | 0.125(x+230)=200 | | -2(3x-5)= | | 2y+16=180 | | 2(2y+16)=7y-7 | | 188-5x=40x+18 | | (3z+5)+(2z-10)+90=180 | | 3n-5=-(6+5n) | | (4y+8)+(3y-9)+90=180 | | 2(x+1)-x(x+1)=0 | | b-1819=2300 | | 3(d+6)=12(d+3) | | -1.3+0.4= | | 12x+20=3x+209 | | 4x+10=2(3x-11) | | 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) |

Equations solver categories